2011
DOI: 10.1039/c0ob01119c
|View full text |Cite
|
Sign up to set email alerts
|

Iron-catalyzed sulfonyl radical formations from sulfonylhydrazides and oxidative addition to alkenes

Abstract: Generation of sulfonyl radicals from sulfonylhydrazides has been achieved in the presence of a non-toxic iron catalyst and oxygen. The intermolecular addition of resultant sulfonyl radicals to alkenes affords β-hydroxysulfone compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(63 citation statements)
references
References 17 publications
2
58
0
3
Order By: Relevance
“…896 A radical mechanism was discussed which involves the formation of sulfonyl radicals by stepwise single-electron oxidations by Fe(III) and loss of dinitrogen. Addition of the sulfonyl radical to the alkene and trapping of the resulting alkyl radical by oxygen provides peroxy radicals which are reduced by the generated Fe(II) species to afford the hydroxy group.…”
Section: Càheteroatom Bond Forming Additions To Càc Double and Triplementioning
confidence: 99%
“…896 A radical mechanism was discussed which involves the formation of sulfonyl radicals by stepwise single-electron oxidations by Fe(III) and loss of dinitrogen. Addition of the sulfonyl radical to the alkene and trapping of the resulting alkyl radical by oxygen provides peroxy radicals which are reduced by the generated Fe(II) species to afford the hydroxy group.…”
Section: Càheteroatom Bond Forming Additions To Càc Double and Triplementioning
confidence: 99%
“…Taniguchi group used sulfonyl hydrazides for the production of sulfonyl radicals. The reactions of sulfonyl hydrazides with alkenes were catalyzed with 10 mol% of FeCl 3 in the presence of oxygen to afford β-hydroxysulfones 183 (Scheme 81) 144. The Li group reported that Bu 4 NI (TBAI) and t-butyl hydroperoxide (TBHP) catalytic system could be used to generate sulfonyl radicals from sulfonyl hydrazides for the reactions of α-substituted styrenes to form allylic sulfones 184 (Scheme 82) 145.…”
mentioning
confidence: 98%
“…The methyl sulfonyl radical generated from DMSO in the presence of catalytic Cu(I) under O 2 atmosphere, was 10 …”
mentioning
confidence: 99%
“…Recent work by Taniguchi has shown that sulfonyl radicals generated from the corresponding hydrazine compounds can be 35 used to functionalize alkenes. 10 Furthermore, Lei has also shown that sulfonyl radicals generated from the corresponding sulfinic acids are useful for the oxidative difunctionalization of alkenes and alkynes. 11 However, as far as we know, there has been no report on the use of methyl sulfonyl radical generated from 40 DMSO in organic synthesis.…”
mentioning
confidence: 99%